Clinical and Radiographic Dependences of Functional Status, Indices of the Hip Joint, and Femur Migration in Children with Cerebral Palsy - Yatsuliak, Mykhailo B.; Nemesh, Mykhailo M.; Martsyniak, Stepan M.; Melnyk, Mykhailo V.; Kabatsii, Miroslaw S.; Filipchuk, Viktor V. (International Journal of Child Health and Nutrition, 2022)
Relevance: Significant incidence of hip pathology in different groups of children with cerebral palsy and factors that may affect its formation are relevant objects of the study. The Goal of the Study: To establish the features of the hip joint’s formation, examining the clinical and radiographic dependences of the functional status and indices of the hip joint in patients with cerebral palsy. Materials and Methods: We conducted a clinical and radiographic examination of the hip joints using our own methods and standard anterior-posterior radiography, and statistical analysis of hip parameters and factors that may have influenced their formation. The total number of patients was 47 persons (86 joints). Results: Correlation relationships have been established between hip parameters and factors that may affect them: Gross Motor Function Classification System (GMFCS), gait function, level of lesion, developmental dysplasia of the hip, and adductor myotomy in medical history. Conclusions: The Reimers’ index showed greater reliability compared to the Wiberg angle. Positioning the patient’s body using our own method can be used to screen the hip joints in cerebral palsy based upon the Reimers index while obtaining the true parameters of the femoral neck-shaft angle and torsion of the femur.